Artificial Intelligence and Education in the Global South - Reimers, Fernando; Azim, Zainab; Palomo, Maria-Renée; Thony, Callysta (Springer Nature, 2025)
This open access book examines the dynamic intersection of artificial intelligence and education in the Global South, where resource constraints and demographic trends create unique challenges and opportunities. Adopting a systems perspective, it explores how AI can transform teaching, curriculum, assessment, teacher professional development, school leadership and system governance while addressing AI literacy, improving the effectiveness of education and developing transferable skills. The book highlights the risks of exacerbating existing inequalities if technology is not carefully integrated and stresses the importance of human-centered, locally adapted solutions. The book examines whether AI is supporting innovation or the transformation of education systems and how it is addressing the principal most vexing challenges with respect to the areas examined. Each chapter draws on an analysis of the potential of AI, on evidence of its use and on evaluation on the implementation and effectiveness of applications. Each chapter concludes with main takeaways for policy and practice, key ethical issues and questions that merit more research.